Higher serum apolipoprotein B level will reduce the bone mineral density and increase the risk of osteopenia or osteoporosis in adults - Zhu, RunJiu; Xu, Yuan; Wang, ZhaoFu; Li, Hui; Song, MingRui; Wan, HaoYang; Yang, Hong; Zhang, Xin; Chai, Yu; Yu, Bin (Frontiers in Cell and Developmental Biology, 2022)
Objestive: There is very limited evidence linking serum apolipoprotein B and lumbar spine BMD in adults aged 20-59 years from the NHANES database. There are few studies linking Apo B concentrations and BMD, and the association between obesity and BMD is subject to some debate. Therefore, the aim of this study was to determine the association between serum Apo B concentrations and BMD in the lumbar spine in adults aged 20-59 years. Methods: A cross-sectional study of the entire US non-institutionalised population was investigated using data from the National Health and Nutrition Examination Survey (NHANES) database. A weighted multiple regression equation model was used to assess the relationship between total apolipoprotein B and lumbar spine BMD. Subsequent stratified analyses were performed to refine the main populations of association. Results: There was no significant correlation between total ApoB and lumbar spine BMD after using a weighted multiple regression model. However, when total Apo B concentrations were quadruple-grouped, there was a significant negative association between Apo B concentrations and lumbar spine BMD when Apo B concentrations were in the Q3 interval (>0.89 g/L, ≤1.07 g/L) and the Q4 interval (:>1.07 g/L). After adjusting for potential confounders. In stratified analyses by sex, there was no statistically significant trend towards a negative correlation between serum Apo B concentrations and lumbar spine BMD in women. In men, there was a strong negative correlation and the results were statistically different. After ethnic stratification, there was no statistically significant difference in the correlation between Apo B and lumbar spine BMD in Mexican American, Non-Hispanic White and Non-Hispanic Black. Conclusions: Our results suggest that the correlation between serum Apo B levels and lumbar spine BMD varies by gender. Elevated serum Apo B levels were negative for bone. For men, elevated Apo B concentrations between 0.65 (g/L) and 1.13 (g/L) had a significant negative impact on bone health.